The Effect of Audio-Visual Media on the Learning Outcomes of Civic Education of Elementary School Students: A Literature Review - Awalidinna, Diva Fadhila; Utama, Candra (Universitas Negeri Malang, 2024)
Attractive and effective learning media play an important role in improving the quality of learning and achieving more optimal educational goals. Among various types of learning media, audiovisual media has been proven effective in learning, as stated in previous research. This study aims to examine the effect of using audiovisual media on civic education learning outcomes of elementary school students. The methodology used is descriptive qualitative with literature review method. Of the 20 journals collected, 12 journals met the research criteria. Based on the literature review, it was found that 50% of the previous studies used experimental methods, and the remaining 50% used classroom action research methods. The research sample consisted of various grade levels, with the largest group in grade four. Observation sheets and questions related to the learning material were used as measurement tools to assess student learning outcomes. The research results from the review process show that audio-visual media is very effective in increasing students' participation and understanding in learning.